Powered endoscopic endonasal dacrocystorhinostomy using inferiorly based mucosal flap: our experience - Bandadka, Ramya; Munnur Haridas, Suprabha; Mylanahalli Doddarangaiah, Prakash (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: The most critical element for successful management of lacrimal system pathology distal to common canaliculus that requires endoscopic endonasal dacrocystorhinostomy (EEDCR) is the creation of widest possible marsupialisation of the medial wall of the lacrimal sac. With minor modifications and simplication of the original technique of EEDCR, common surgical failures like obstruction of neo-ostium by granulation tissue or infolding of flap can be avoided. To determine the success of EEDCR using inferiorly based mucosal flap, removal of overlying bone using Kerrison’s punch followed by vertical incision of the medial wall of lacrimal sac with microdebrider assisted trimming of the lacrimal sac flaps. Methods: A total of 31 patients with epiphora secondary to nasolacrimal duct obstruction (NLDO) were operated using the above technique with 3 bilateral cases amounting to a total of 34 procedures. The surgical outcome and long term patency of neo-ostium were evaluated. Results: Of the 34 procedures, 32 procedures (94.1%) had complete resolution of epiphora at the end of one year follow up. The 2 failures were due to canaliculitis. Conclusions: Powered EEDCR with trimming of medial wall of lacrimal sac and inferiorly based mucosal flap preservation to cover the exposed part of bone is a simple procedure with favourable long term outcome.